Cultural Value of “A’bulo Sibatang” in Social Studies Learning as Cultural Heritage to Build Ecological Intelligence of Junior High School Students - Hasni, Hasni; Falihin, Dalilul; Ibrahim, Ibrahim; Nur, Rahmania; Bte Salman, Nola Febriyani (International Journal of Social Learning (IJSL), 2024)
Cultural values are an important aspect in the context of Social Studies learning. This study aims to determine the cultural values of a'bulo sibatang that can be integrated into social studies learning as an effort to build students' ecological intelligence and the impact of inheriting the cultural values of a'bulo sibatang in building the ecological intelligence of students. The type of research used is descriptive qualitative with a phenomenological approach. Observation, interview, and documentation data collection techniques. The results showed three cultural values of a'bulo sibatang that can be integrated into social studies learning: the value of sipakatu, siapakainga, and assamaturukang values.  Integration of a'bulo sibatang values in social studies learning is very effective in building ecological intelligence of junior high school students through social project activities, which are written in the media mading. The cultural value of a'bulo sibatang has a very positive impact on building the ecological intelligence of junior high school students.